Did A Fruit and Vegetable Incentive Program Support low-income Households in North Carolina during the COVID-19 Pandemic? A Mixed Methods Assessment of the Healthy Helping Program and Other Pandemic-Related Food Assistance. Issue 3 (4th May 2023) - Lu, Isabel; Sheppard, Brett; Ng, Shu Wen; Burstein, Sarah; Charles, Emile; Williams, Taylor; De Marco, Molly
ABSTRACT: In 2020, the Healthy Helping Fruit and Vegetable Program provided SNAP-eligible beneficiaries with $40/month, for up to 3 months, to purchase fruits and vegetables at a chain supermarket in North Carolina. A survey to describe participants' experiences with the program and interviews to explore whether these experiences were shaped by participating in other pandemic-related food access programs were conducted. In conjunction with other food access programs,  programs that allow participants freedom to choose what they purchase may alleviate household hardships and provide greater access to nutrient-dense foods during the COVID-19 pandemic and beyond.